Implementación de seguridad en las transacciones de pago realizadas a través de dispositivos móviles utilizando la tecnología NFC. - Briceño Merino, Nixon Camilo (2021)
This Degree Project consists of securing data transmission through NFC technology by implementing the cryptographic algorithm called Elliptic Curves (ECC). To select this algorithm, a Systematic Literature Review was carried out following the methodology proposed by Barbara Kitchenham [1]. When the encryption algorithm was determined, a mobile application was developed using the agile methodology Extreme Programming (XP), for the development of this application the use of NFC technology was considered, which allows a simple and secure communication between devices that are in a distance up to ten centimeters. The algorithm used was ECC with curve 25519. For the testing phase, a system was set up using hardware and software components, an Arduino Mega 2560 was used, to which a PN532 module was added for NFC communication and a SIM900 module to send data to the server. Two scenarios were proposed: one called “insecure”; where the cryptographic algorithm was not used and another called “secure”; where ECC was implemented, the results are presented according to the objectives set for the present Degree Project. Finally, in the discussion section, the development of an alternative proposal and the technical and economic environmental evaluation were presented. Keywords: NFC, Near Field Communication, cryptographic algoritms, cryptography and mobile payment.